2008
DOI: 10.1038/bjp.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

Contractile properties of the pig bladder mucosa in response to neurokinin A: a role for myofibroblasts?

Abstract: Background and purpose: The bladder urothelium is now known to have active properties. Our aim was to investigate the contractile properties of the urinary mucosa in response to the tachykinin neurokinin A (NKA) and carbachol. Experimental approach: Discrete concentration-response curves for carbachol and NKA were obtained in matched strips of porcine detrusor, mucosa and intact bladder, suspended in organ baths. The effects of inhibitors and tachykinin receptor antagonists were studied on NKA-mediated contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 29 publications
(42 reference statements)
6
52
0
Order By: Relevance
“…In a recent study we showed that isolated strips of U&LP from the pig bladder dome can also contract in response to neurokinin A and muscarinic receptor stimulation, the responses to NKA being mediated via NK2 receptors (Sadananda et al, 2008). These tissues from the dome of the bladder also develop spontaneous phasic contractions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a recent study we showed that isolated strips of U&LP from the pig bladder dome can also contract in response to neurokinin A and muscarinic receptor stimulation, the responses to NKA being mediated via NK2 receptors (Sadananda et al, 2008). These tissues from the dome of the bladder also develop spontaneous phasic contractions.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to releasing ATP and other mediators, the U&LP of the pig bladder (Sadananda et al, 2008) and the lamina propria of the rabbit urethra (Mattiasson et al, 1985, Zygmunt et al, 1993) display contractile properties and have been shown to contract in response to a number of agonists. It is presently unclear which specific cell types mediate contraction, but it has been suggested that myofibroblasts may be involved (Sadananda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tension responses to neurokinin A and carbachol are present after fine dissection and removal of smooth muscle from the preparations and it has been suggested that myfibroblasts may be involved. 5,8 In addition, spontaneously generated electrophysiological events have been observed in myofibroblasts located within the lamina propria. 26 The function of this contractile activity is also uncertain.…”
Section: β-Adrenoceptorsmentioning
confidence: 99%
“…This inner region of the bladder wall has a barrier function, but also when stretched it releases a number of factors that influence detrusor contraction and afferent nerve sensitivity. 3 In addition, the urothelium with lamina propria from the dome of the pig bladder 4,5 and also strips of lamina propria from the rabbit urethra 6,7 have been shown to contract to agonists such as carbachol, neurokinin A and noradrenaline. Isolated strips of urothelium with lamina propria also develop spontaneous contractile activity, with carbachol and also stretch-induced release of acetylcholine mediating increases in spontaneous contractile frequency via M 3 receptors.…”
Section: Introductionmentioning
confidence: 99%